Waxy endosperm corn in growing and finishing rations for swine - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs fed rations containing waxy endosperm corn and those fed normal corn responded similarly in digestion and growing trials. Likewise, finishing pigs responded similarly when fed the two corns in digestion and growing trials.
Swine Industry Day 1974 is known as Swine Day, 1974
Keywords: Swine; Waxy endosperm corn; Finishing pigs